Revision of the genus Penthoscapha Heller (Coleoptera, Curculionoidea, Entiminae, Eupholini) with notes on the genera of Eupholini from New Guinea - Riedel, Alexander (Zootaxa, 2009)
A preliminary key to the genera of Papuan Eupholini is given. The hitherto monotypic subgenus Niphetoscapha Heller 1914 is transferred from Rhinoscapha Montrouzier 1855 to Gymnopholus Heller 1901: Gymnopholus (Niphetoscapha) wichmanni (Heller), comb. n.. It is closely related to G. audax Gressitt 1966 and G. nitidus Gressitt & Sedlacek 1967 which are moved from the subgenus Symbiopholus Gressitt 1966 to Niphetoscapha. The record of the genus Celebia Thomson 1857 for New Guinea is reported as erroneous. The genus Penthoscapha Heller from montane and subalpine habitats of the central mountains of West New Guinea is revised. A lectotype is designated for the type-species, P. lorentzi Heller, 1914. Penthoscapha toxopei (Gressitt & Sedlacek 1967), comb. n. is transferred from Gymnopholus. Four new species of Penthoscapha are proposed: P. doormanensis sp. n., P. gerhardschereri sp. n., P. pulverea sp. n., P. similis sp. n.. All species of Penthoscapha are described, a key is provided, and their distribution is mapped. Reduction of hind wings in Penthoscapha and fusion of elytra in P. gerhardschereri are interpreted as consequences of flightlessness. Extracuticular pigments are described and illustrated for P. doormanensis, P. gerhardschereri, and P. pulverea. The phylogenetic placement of Penthoscapha among Eupholini is briefly discussed.